2016
DOI: 10.1002/jgt.22032
|View full text |Cite
|
Sign up to set email alerts
|

Planar Digraphs of Digirth Five Are 2‐Colorable

Abstract: Neumann-Lara (1985) andŠkrekovski conjectured that every planar digraph with digirth at least three is 2-colorable, meaning that the vertices can be 2-colored without creating any monochromatic directed cycles. We prove a relaxed version of this conjecture: every planar digraph of digirth at least five is 2-colorable. The result also holds in the setting of list colorings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 3 publications
(9 reference statements)
1
19
0
Order By: Relevance
“…Then G − X is acyclic. If g = 5 we have |X| |A| = |C| 2n−5 4 and if g 6, we have |X| |A| = |C| 2n−6 g , as desired. Assume now that g = 4.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Then G − X is acyclic. If g = 5 we have |X| |A| = |C| 2n−5 4 and if g 6, we have |X| |A| = |C| 2n−6 g , as desired. Assume now that g = 4.…”
mentioning
confidence: 79%
“…A feedback vertex set in a digraph G is a set X of vertices such that G−X is acyclic, and the minimum size of such a set is denoted by τ (G). In this short note, we study the maximum f g (n) of τ (G) over all planar digraphs G on n vertices with digirth g. Harutyunyan [1,4] conjectured that f 3 (n) 2n 5 for all n. This conjecture was recently refuted by Knauer, Valicov and Wenger [5] who showed that f g (n) n−1 g−1 for all g 3 and infinitely many values of n. On the other hand, Golowich and Rolnick [3] recently proved that f 4 (n) 7n 12 , f 5 (n) 8n 15 , and f g (n) 3n−6 g for all g 6 and n. Harutyunyan and Mohar [4] proved that the vertex set of every planar digraph of digirth at least 5 can be partitioned into two acyclic subgraphs. This result was very recently extended to planar digraphs of digirth 4 by Li and Mohar [6], and therefore f 4 (n) n 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The list dichromatic number χfalse(Dfalse) of D is the smallest integer k such that D is L ‐colorable for any k ‐list‐assignment L . We note that the definition of list coloring of digraphs is not quite new as it first appeared in where the authors derived an analog of Gallai's theorem for digraphs, as well as in . Our goal in this article is to initiate the study of the list dichromatic number.…”
Section: Introductionmentioning
confidence: 99%
“…An oriented graph is a digraph D without loops and multiple arcs. An acyclic set in D is a set of vertices that induces a directed subgraph without directed cycles.The complement Acyclic set 2n 5 [2] 5n + 6 12 [5] n 2 [4] n(g − 3) + 6 g [5] of an acyclic set of D is a feedback vertex set of D. A question of Albertson, which was the problem of the month on Mohar's web page [6] and was listed as a "Research Experience for Graduate Students" by West [11], asks whether every oriented planar graph on n vertices has an acyclic set of size at least n 2 . There are three independent strengthenings of this question in the literature.…”
Section: Introductionmentioning
confidence: 99%